Chapter Ancora su Boccaccio copista di Dante: (almeno) tre 'redazioni' della Vita nuova - Giglio, Lorenzo (Studi e saggi, 2021)
The paper studies the editorial practice of Boccaccio in his copies of Dante's Vita Nuova, through a textual comparison between the two preserved transcriptions and the ones that are only hypothetically referable to his work, thanks to an examination of the varia lectio. What emerged for Vita Nuova from a new comprehensive collatio of the most important witnesses of Boccaccio's manuscript tradition, put together with what is known about the other Dante's works copied by Boccaccio himself (lyrics and Commedia), seem to converge in the hypothesis, already suggested by Michele Barbi, that around the interpositus b3 it is quite recognizable a third "authorial edition", originally conceived like the other two, and perhaps currently surviving in the manuscript Riccardiano 1035.